2013
DOI: 10.1111/vco.12046
|View full text |Cite
|
Sign up to set email alerts
|

The radiosensitizing effect of the aurora kinase inhibitors, ENMD‐2076, on canine mast cell tumours in vitro

Abstract: ENMD-2076 is an aurora kinase inhibitor that also has multi-target tyrosine kinase inhibitor properties. In this study, the mRNA and the protein expression of aurora-A and aurora-B were evaluated in three canine mast cell tumor cell lines. Dose dependent cytotoxicity was seen in the cells treated, and it affected the cell cycle with cells in the G2/M phase being selectively killed. The cells were also evaluated for radiosensitivity with/without ENMD-2076, and radiosensitization was seen after 3 Gy and 6 Gy exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However, the results of another study [ 30 ] were in contrast to those of our study and showed that patients with Aurora-A overexpression had better clinical and histological response to CCRT. In some in vitro studies, inhibition of Aurora-A potently inhibited proliferation of atypical teratoid/rhabdoid tumor cells [ 31 ], glioblastoma neurosphere tumor cells [ 32 ], canine mast cell tumor cells [ 33 ] and sensitized these cells to radiation. In both in vitro and in vivo models of human cancers, including hepatocellular carcinoma[ 34 ], androgen-insensitive prostate cancer [ 35 ], oral squamous cell carcinoma [ 36 ] and lung cancer [ 37 ], some novel small molecule Aurora-A inhibitors showed radiation sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of another study [ 30 ] were in contrast to those of our study and showed that patients with Aurora-A overexpression had better clinical and histological response to CCRT. In some in vitro studies, inhibition of Aurora-A potently inhibited proliferation of atypical teratoid/rhabdoid tumor cells [ 31 ], glioblastoma neurosphere tumor cells [ 32 ], canine mast cell tumor cells [ 33 ] and sensitized these cells to radiation. In both in vitro and in vivo models of human cancers, including hepatocellular carcinoma[ 34 ], androgen-insensitive prostate cancer [ 35 ], oral squamous cell carcinoma [ 36 ] and lung cancer [ 37 ], some novel small molecule Aurora-A inhibitors showed radiation sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…ENMD-2076 (EntreMed) has a 25-fold better selectivity for AURKA over AURKB, and an IC50 of 14 nM [135], although an inhibitory activity towards multiple kinases has been described for this compound [135]. In vitro experiments revealed that ENMD-2076 induces a G2/M checkpoint block and cell death, alone or in combination with radiosensitisation [136]. Phase I trials showed that ENMD-2076 is a lowcytotoxicity compound in patients affected with relapsed or refractory acute myeloid leukaemia, or chronic myelomonocytic leukaemia [137].…”
Section: Enmd-2076mentioning
confidence: 99%
“…As soon as a strong link between Aurora-A and cancer was found, many pharmaceutical companies quickly started trying to develop Aurora-A inhibitors for cancer treatment. Inhibitors of Aurora kinases, such as MLN8237 (8), MK-5108 (9), and ENMD-2076 (10), have been developed but none have yet gone beyond Phase III trials (5), suggesting the functions of Aurora-A have not been fully understood in cancer cells. More importantly, in a complex organism, Aurora-A is an oncogene in mammary epithelium and glands (11, 12), whereas it could be a tumor suppressor in neural stem cells (13), so it should be considered that Aurora-A has cell type-specific functions.…”
Section: Introductionmentioning
confidence: 99%